Monetary policy and transaction costs: Empirical analysis of consumption function for the United States of America (1988-2014) - Carlos Eduardo Gomes; Maria Helena Ambrosio Dias (EconomiA, 2020)
In macroeconomic theory, different approaches discuss the ability of monetary policy to affect real variables in the long run. This research proposes the empirical application of a theoretical model that includes nominal rigidities arising from transaction costs and real rigidities arising from the firms' competition structure. Thus, based on data from the US economy we propose to test the theoretical results combining the existence of shocks arising from both real factors and factors affecting the money market, establishing tests for shocks of supply and aggregate demand. The concern is to investigate if the economic policy is capable of affecting the long run (average) values of the real private consumption. Time series analysis methodology of Structural Vector Autoregressive (SVAR) models was used to test long run relationship for US economy. The ability to establish the long run relationships between these aggregates with some degree of confidence, allow simulating shocks by impulse response functions and variance decomposition. The theoretical results of the model indicate that productivity, transaction costs (number of transactions with credit/debit cards) and currency money tend to positively influence consumption, whereas delinquency have a negative effect on consumption. We tested two empirical specifications and both confirmed the theoretical results for the US economy and, therefore, the research can help policymakers to measure the long run consequences of their decisions, that is, the results converge on the non-neutrality of money in the long run in the US economy.
Keywords: C32; E21; E52; 330; Monetary policy; Policymakers; Transaction costs; SVAR; US economy